Cyberpragmatics Analysis of Emoji Language in TikTok - Natasya Miranda Gihar; Afia Nur Meiza; Najla Regar; Khairunnisa; Siregar, Deasy Yunita (Universitas Negeri Medan, 2024)
This study aims to uncover the different meanings embedded in the various emojis used on TikTok, with a particular focus on their pragmatic implications. This article uses a qualitative descriptive methodology to investigate the cyberpragmatic aspects of emoji within TikTok’s linguistic landscape and provides a comprehensive understanding of how emoji contribute to the broader pragmatic context within TikTok’s unique language ecosystem. The investigation involved examining various TikTok interactions to determine the intricacies of communications conveyed through emojis. It is hoped that these findings can explain how complex the function of emoji is as a pragmatic tool in expressing meaning in the TikTok language community. Keywords: Emoji, Cyberpragmatics, Language, Tiktok